Comparison of retention in removable partial denture clasps made of chrome-cobalt and PolyetheretherKetone (an in-vitro study) - عثمان نرمين; محمود محمود (Latakia University Journal -Medical Sciences Series, 2024)
Aim: comparison of retentive force between Roach clasps made of PEEK and Roach clasps made of chrome-cobalt, comparison of the changes in retentive force for the clasps after insertion removal cycles. Materials and Methods: the research sample involved 16 clasps (8 Roach clasps made of PEEK, 8 Roach clasps made of chrome-cobalt). Each abutment was prepared to receive two clasps. The abutments were scanned to design the clasps that have the same dimensions. After manufacturing the clasps, retentive force was evaluated 3 times (initial retention- after 1095 cycles- after 3285 cycles). Results: In comparison of chrome- cobalt clasps with PEEK clasps, PEEK clasps showed significantly lower retentive force than CoCr clasps. All clasps showed a significant decrease in retentive force. Conclusions: PEEK material can be used in manufacturing of partial denture clasps. Metal clasps have higher retention than PEEK clasps. All clasps lose its retention over time.